Phenotypic differentiation of the slow worm lizards (Squamata: Anguis) across their contact zone in Central Europe - Benkovský, Norbert; Moravec, Jiří; Gvoždíková Javůrková, Veronika; Šifrová, Helena; Gvoždík, Václav; Jandzik, David (PeerJ, 2021)
BACKGROUND: The application of molecular-phylogenetic approaches to taxonomy has had a dramatic effect on our understanding of the diversity of reptiles. These approaches have allowed researchers to reveal previously hidden lineages as well as taxonomic overestimation in morphologically plastic taxa. Slow worms, legless lizards of the genus Anguis (Squamata: Anguidae), were previously considered to comprise either one or two species, and morphology-based intraspecific taxonomy of Anguis fragilis remained controversial throughout the 20th century. After the discovery of deep genetic divergences within the genus, its taxonomy was reconsidered, and as a result, five extant species have been recognized. In order to better understand the patterns of their interspecific differentiation, here we studied phenotypic differences between the two most widespread of them-A. fragilis and A. colchica, and their putative hybrids across the contact zone of both species in Central Europe. METHODS: We used multivariate and univariate statistics and analyzed ten metric, eleven meristic, and six categorical phenotypic variables in material comprising a total of 326 individuals. We also genotyped individuals from the contact zone for one mitochondrial and two nuclear DNA fragments in order to delineate the distribution of individuals of hybrid and non-hybrid origin. The clines in morphological traits were studied using HZAR. RESULTS: We show that the two species are morphologically differentiated. Anguis fragilis has a less robust head, fewer scales covering the body, lower frequency of the external ear opening presence, lower frequency of separated prefrontal scales, higher frequency of prefrontal scales in contact with each other, and body coloration more similar to the juvenile coloration than A. colchica. Slow worms from the contact/hybrid zone are characterized by an intermediate morphology, with more similarities to A. fragilis than to A. colchica. DISCUSSION: None of the analyzed characters alone proved to be fully diagnostic, although more than 90% of all individuals could be successfully assigned to one or another species based on numbers of scales around the body. Our results indicate concordant, coincident, and steep clines in character states change. We present several hypotheses on the origin and evolutionary maintenance of the morphological divergence between both species and suggest that different evolutionary histories of the taxa rather than recently acting selection explain the observed morphological variation.
Keywords: Lizards; Morphology; Coloration; Diversity; Western Palearctic; Reptilia; Hybrid zone; Sauria; Morphometrics; Hybridization